PENGARUH PARTISIPASI MANAJEMEN, PELATIHAN DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI (STUDI KASUS PADA PT.PJB UNIT BISNIS JASA O & M SE INDONESIA) - Awaliyah, Awaliyah; Alliyah, Siti (JAB (Jurnal Akuntansi & Bisnis), 2017)
This research aims to examine, analyze the effect of management participation, training and utilization of information technology on the effectiveness of accounting information systems at PT PJB O & M Services Business Units throughout Indonesia. The sample used in this research are employees who use SIA at PT PJB O & M Services Business Units throughout Indonesia. Hypothesis testing in this research using multiple linear regression analysis. Data were analyzed using SPSS version 19. The results of this research showed that: (1) management participation had a significant negative effect on the effectiveness of SIA, (2) training had no significant negative effect on the effectiveness of SIA, (3) the use of information technology had a significant positive effect on the effectiveness of SIA. The coefficient of determination of 15.6% indicates that the effectiveness of SIA contained in PT PJB O & M Services Business Units throughout Indonesia is able to be explained by the variables of management participation, training and utilization of information technology by 15.6% and the remaining 84.4% able explained by other factors outside the research model. Keywords:    Management Participation, Training, Information Technology    Utilization and Effectiveness of Accounting Information Systems